Soil Fertility Status of Some Soil Orders and NuMaSS Fertilizer Recommendation at Bench-Maji Zone, South West, Ethiopia - Abitew, Masresha; Kebebew, Solomon (Canadian Journal of Agriculture and Crops, 2016)
The study was carried out to evaluate the fertility status of some soil orders in Bench Maji zone districts and to determine the amount of N and P fertilizer being recommended for maize across locations using NuMaSS for better crop production and productivity. A total of 16 surface and profile soil samples were collected from four locations or soil orders and analyzed for the selected soil physical and chemical properties and Nutrient Management Decision Support System (NuMaSS) was used as diagnostic tool to recommend N and P fertilizers for maize across the locations. Soil of Gurafarda, Debub-Bench, Mianit-Goldia had no exchangeable Ca2+, Mg2+ and K+ problems but the soil of Semenh-Bench had low Ca2+, medium Mg2+ and deficient to marginal K+ contents.Thus; the soil in Semenh-Bench probably requires improvements of these cations. The result revealed that the sampled soils of all locations showed, a serious nutrient limiting status and available P. The soil pH-H2O was also below the critical level in the sampled soils. Moreover, high probabilities of N and P deficiency were observed in all locations this correspondingly required higher rate of fertilizer dosage as depicted by NuMaSS. Finally, 68 kg N/ha and 67 kg P/ha, 0 kg N/ha and 52 kg P/ha, 98 kg N/ha and 47 kg P/ha, and 69 kg N/ha and 0 kg P/ha fertilizer rates were recommended using NuMaSS for maize at soils of Semenh-Bench, Gurafarda, Debub-Bench and Mianit-Goldia, respectively. Besides, the nutrient recommendation, other management activity for the amelioration of these acidic soils is advisable. In general, management activities for these soils should be practiced and appropriate strategies for which should be determined according to the crops being grown.